2022
DOI: 10.16955/bitkorb.1130635
|View full text |Cite
|
Sign up to set email alerts
|

Screening of snap and dry bean (Phaseolus vulgaris L.) genotypes for resistance to Bean common mosaic virus and Bean common mosaic necrosis virus

Abstract: The most effective control of Bean common mosaic virus (BCMV) and Bean common mosaic necrosis virus (BCMNV) is achieved by using the seeds of resistant cultivars. During conventional breeding, resistance against BCMV and BCMNV in common bean can be developed by pyramiding the strain-nonspecific dominant I gene with strain-specific recessive (bc-) resistance genes for long-term virus control. In this study, a total of 58 bean genotypes involving registered green and dry bean cultivars, local genotypes, and bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…The two pathotypes (III and VI) identified in this study have been reported in Kenya (Mangeni et al 2014;Mutuku et al 2018). The DAS-ELISA was useful in detecting BCMNV in asymptomatic plants, similar to previous studies (Kilic et al 2020;Mangeni et al 2020;Deligöz et al 2022). The three dry bean cultivars (MCM 1015, MCM 2001 andMCM 5001) used as resistant checks consistently showed resistance, confirming their resistance to BCMNV.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The two pathotypes (III and VI) identified in this study have been reported in Kenya (Mangeni et al 2014;Mutuku et al 2018). The DAS-ELISA was useful in detecting BCMNV in asymptomatic plants, similar to previous studies (Kilic et al 2020;Mangeni et al 2020;Deligöz et al 2022). The three dry bean cultivars (MCM 1015, MCM 2001 andMCM 5001) used as resistant checks consistently showed resistance, confirming their resistance to BCMNV.…”
Section: Discussionsupporting
confidence: 88%
“…The differences observed in disease pressure at the two sites could be attributed to factors such as genotype susceptibility in terms of symptom expression, strains of the virus, and environmental factors such as humidity and temperature (Muute et al 2021). The symptoms of BCMNV observed in this study are similar to previous studies (Mwaipopo et al 2018;Mangeni et al 2020;Deligöz et al 2021Deligöz et al , 2022. However, some cultivars were asymptomatic under field conditions, highlighting the need for artificial inoculation under controlled conditions and subsequent confirmation using ELISA tests on all genotypes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…SCAR markers were utilized to investigate the presence of the dominant I and recessive bc-1 2 genes in a set of 204 dry bean breeding lines (Deligöz et al, 2021). Very recently, Deligöz et al (2022) screened I+bc-1 2 genes in 58 common bean genotypes using SBD-5 and SW-13 markers, respectively. Out of the tested genotypes, 31 had both the dominant I gene and bc-1 2 specific products.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, various specific markers associated with resistance genes were reported such as SW-13 SCAR (Sequence-characterized Amplified Regions) marker for I gene, ROC11 SCAR marker for bc-3 gene, and SBD-5 SCAR marker for the bc-1 2 gene by Melotto et al (1996), Miklas et al (2000) and Johnson et al (1997), respectively. These markers were used to discover desired genes to develop common bean varieties resistant to BCMV/BCMNV in diverse investigations (Deligöz ve Sökmen, 2013;Pasev et al, 2014;Yeken et al, 2018;Palacıoğlu et al, 2020;Deligöz et al, 2022). While previous studies have identified desirable genes for BCMV/BCMNV in various genetic resources within Türkiye, conducting a comprehensive investigation across different germplasm collections is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%